2012
DOI: 10.1016/j.jand.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Nutrition Education Intervention to Improve Carbohydrate Counting in Adolescents with Type 1 Diabetes Study: Is More Intensive Education Needed?

Abstract: Background and Objectives Youth with type 1 diabetes do not count carbohydrates (CHOs) accurately, yet it is an important strategy in blood glucose control. The study objective was to determine whether a nutrition education intervention would improve CHO counting accuracy and glycemic control. Design Randomized, controlled, nutrition intervention trial recruited February 2009 to February 2010. Participants and Methods Youth (12-18 years, n=101) with type 1 diabetes were screened to identify those with poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 21 publications
2
61
0
1
Order By: Relevance
“…Furthermore, clinical experience suggests that patients may manually calculate their insulin dose, rather than enter the number of carbohydrates consumed into their insulin pump, which would not be captured as a mealtime dose. Similarly, as noted by the authors, adolescents commonly ''guesstimate'' carbohydrate values, either over-or underestimating carbohydrate grams in a given meal, 9 so that the bolus does not match actual intake, making it a less perfect measure of adherence. Another potential pitfall of the BOLUS measure is that adolescents and young adults may eat more erratically, or snack more often than younger children, especially in the evenings.…”
mentioning
confidence: 74%
“…Furthermore, clinical experience suggests that patients may manually calculate their insulin dose, rather than enter the number of carbohydrates consumed into their insulin pump, which would not be captured as a mealtime dose. Similarly, as noted by the authors, adolescents commonly ''guesstimate'' carbohydrate values, either over-or underestimating carbohydrate grams in a given meal, 9 so that the bolus does not match actual intake, making it a less perfect measure of adherence. Another potential pitfall of the BOLUS measure is that adolescents and young adults may eat more erratically, or snack more often than younger children, especially in the evenings.…”
mentioning
confidence: 74%
“…In an outpatient environment, individual experience commonly leads to adjustments for meals high in fat or protein, although current guidelines account only for carbohydrate. 34 Thus, some study participants may bolus more insulin than needed for high-protein meals, with or without correct carbohydrate counting, 35 resulting in greater hypoglycemia risk. However, this is speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that carbohydrate counting is effective for people with type 1 diabetes 88 and that people can be taught to estimate carbohydrate reasonably accurately. 89,90 In a recent qualitative review of participants who had undergone the DAFNE course, it was revealed that flexible insulin therapy had led some patients to severely restrict carbohydrate as they found that large amounts of carbohydrate coupled with large insulin doses led to unpredictable blood glucose results. 91 Many of the participants reported finding FIIT to be very difficult in practice due to the challenge of estimating the carbohydrate contents of different foods.…”
Section: Type 1 Diabetesmentioning
confidence: 99%